LEXICAL MINIMALISM AND SYNTACTIC SIMPLICITY IN HEMINGWAY’S “THE OLD MAN AND THE SEA” (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article investigates the role of lexical minimalism and syntactic simplicity in Ernest Hemingway’s novella The Old Man and the Sea. By analyzing the author’s distinctive narrative style through the lens of stylistics and syntax, the study reveals how Hemingway’s concise vocabulary and streamlined sentence structures contribute to the emotional depth, thematic resonance, and symbolic strength of the novella. The research highlights how minimal language choices shape readers’ perceptions and subtly guide the emotional atmosphere of the story. The article contributes to broader discussions on how minimalism in language can yield maximum literary impact.